(untitled) (Jurnal Teknodik, 2025)
The Merdeka Mengajar Platform was developed by the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek) to support teachers in accessing references, inspiration, and pedagogical understanding necessary for the implementation of the Merdeka Curriculum. Since its introduction, the Merdeka Mengajar Platform (PMM) has been disseminated and utilized by educators as part of the national effort to strengthen curriculum implementation. However, according to the utilization dashboard, a considerable proportion of educational institutions—approximately 44.25% of a total of 430,000 institutions—remain categorized as “PMM usage needs improvement” (based on data from data.kemdikbud.go.id, accessed on August 2, 2024). To capture users’ responses and identify challenges encountered during the use of the platform, an evaluation was conducted employing the Technology Acceptance Model (TAM) framework. The study was carried out across 38 provinces and involved teacher respondents from various educational levels, including early childhood education (PAUD), kindergarten (TK), elementary (SD), junior high (SMP), senior high (SMA), and vocational schools (SMK), during the period of June–July 2024. The findings indicate that PMM is generally perceived as easy to use, with only a small number of users experiencing technical or operational barriers, largely due to the availability of adequate infrastructure and facilities. The platform is also considered beneficial in supporting teachers’ professional tasks. Nonetheless, several challenges were identified, including limited time for engagement, unstable internet connections, login difficulties, and partial understanding of certain features, although the proportion of affected users remains relatively small. Based on these findings, several recommendations are proposed to enhance PMM utilization, including the development of additional content tailored to teachers’ needs and the integration of a comment or feedback feature to facilitate direct user input for continuous platform improvement.